Lower Paleozoic ‘El Nihuil Dolerites’: Geochemical and Isotopic Constraints of Mafic Magmatism in an Extensional Setting of the San Rafael Block, Mendoza, Argentina - Cingolani, Carlos Alberto (2017)
The ‘El Nihuil Mafic Unit’ is exposed at the Loma Alta region northwards of the El Nihuil dam. This igneous body consists mainly of mafic rocks assigned to the Precambrian and Lower Paleozoic according to different authors. The mafic unit shows an elongated shape with aNNE–SSWorientation on the western side of the San Rafael Block (SRB), developed for a length of 17.5 km and with a maximum width of 4.2 km and is composed of deformed gabbros, amphibolites, and tonalites that represent the Mesoproterozoic continental crust, and dykes and sills of undeformed Lower Paleozoic porphyritic dolerites. We present the petrology, geochemistry, isotope data, and determinations of emplacement conditions of the dolerites that could represent a sliver of Cuyania-Chilenia terranes suture. The dolerites show classical porphyritic texture, with elongated subhedral plagioclase (andesine) and clinopyroxene phenocrysts. Geochemical analyses of El Nihuil Dolerite samples indicate that the rocks are MORB-type basalts. In the P2O5 versus Zr diagram, the dolerites plot in the tholeiitic field similarly to western Cuyania basalts, and in the Th–Hf/3–Ta tectonic discrimination diagram the dolerite dykes plot mainly as E-MORB. Dolerite samples were dated byK–Ar (whole rock) systematic and the ages are 448.5 ± 10 and 434.2 ± 10 Ma (Upper Ordovician and close to the Lower Silurian boundary). The dolerites represent the unique Lower Paleozoic mafic rock outcrops within the SRB. Nd(TDM) ages are in between 0.51 and 0.80 Ga; εNd(0) record positive values ranging from +3.85 and +7.84; εNd(t) record +4.27 to +12.42. 87Sr/86Sr ratios are in between 0.7032 and 0.7050 in agreement with values for ocean ridge tholeiites. These mafic rocks are interpreted as a part of a dismembered ‘Famatinian ophiolite belt’ emplaced during the Lower Paleozoic extensional environment within a thinned Mesoproterozoic continental crust on western Cuyania terrane.